FAKTOR-FAKTOR YANG MEMPENGARUHI LUAS PENGUNGKAPAN CORPORATE GOVERNANCE - Oktaviani, Ita; Priyadi, Maswar Patuh (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is aimed to test the influence of profitability, board of commissioner size, size, leverage, firm age, and dispersion ownership to the wide range of corporate governance disclosure through annual statement which has been prepared by service companies which engagein the field of finance which are listed in Indonesia Stock Exchange.The population has been obtained by using purposive sampling method onthe service companies which engage in the field of finance which are listed in Indonesia Stock Exchange (IDX) in 2011-2015 periods and based on the predetermined criteria 56 service companies have been selected as samples. The analysis method has been conducted by using multiple linear regressions.The result of the model feasibility test shows that simultaneously profitability, board of commissioner size, size, leverage, firm size, and dispersion ownership givewide influence to the corporate governancedisclosure. The result of the research shows that partially profitability, board of commissioner size, size, leverage, firm company, and dispersion ownership give positive and wide influence to the corporate governance disclosure.Keywords: Profitability, size, corporate governance.